Rozwiąż:[tex]1) (2x - 7)^{2} - (3x + 2) (3x - 2) =\\2) 4x (x + 2) - (4x + 1) (2x - 7) =\\3) (3x + 5) (3x - 5) - (2x + 4) =\\4) (5x + 1) (5x - 1) + 2 (x - 3)^{2} =[/tex]

Odpowiedź :

Odpowiedź:

1) -5x^2-28x+53

2) -4x^2+34x+7

3) 9x^2-2x-29

4) 27x^2-12x+17

[tex]1) (2x-7)^{2} -(3x+2)(3x-2)=4x^{2} -28x+49-9x^{2} +4=-5x^{2} -28x+53\\2) 4x(x+2)-(4x+1)(2x-7)=4x^{2} +8x-8x^{2} +28x-2x+7=-4x^{2} +34x+7\\3) (3x+5)(3x-5)-(3x+4)=9x^{2} -25-3x-4=9x^{2} -3x-29\\4) (5x+1)(5x-1)+2(x-3)^{2}=25x^{2} -1+2(x^{2} -6x+9)=25x^{2} -1+2x^{2} -12x+18=27x^{2} -12x+17[/tex]

Pozdrawiam.